Intermittent Fasting Protects against Alzheimer’s Disease Possible through Restoring Aquaporin-4 Polarity - Zhang, Jingzhu; Zhan, Zhipeng; Li, Xinhui; Xing, Aiping; Jiang, Congmin; Chen, Yanqiu; Shi, Wanying; An, Li (Frontiers in Molecular Neuroscience, 2017)
The impairment of Aβ clearance in the brain plays a causative role in Alzheimer’s disease. Polarity distribution of aquaporin-4 (AQP4) is important to remove Aβ from brain. AQP4 polarity can be influenced by the ratio of two AQP4 isoforms M1 and M23 (AQP4-M1/M23), however, it is unknown whether the ratio of AQP4-M1/M23 changes in Alzheimer’s disease. Histone deacetylase3 has been reported to be significantly increased in Alzheimer’s disease brain. Moreover, evidence indicated that microRNA-130a possibly mediates the regulation of histone deactylase3 on AQP4-M1/M23 ratio by repressing the transcriptional activity of AQP4-M1 in Alzheimer’s disease. This study aimed to investigate whether intermittent fasting, increasing the level of an endogenous histone deacetylases inhibitor β-hydroxybutyrate, restores AQP4 polarity via microRNA-130a mediated reduction of AQP4-M1/M23 ratio in protection against Alzheimer’s disease. The results showed that intermittent fasting ameliorated cognitive dysfunction, prevented brain from Aβ deposition and restored the AQP4 polarity in a mouse model of Alzheimer’s disease (APP/PS1 double transgenic mice). Additionally, intermittent fasting down-regulated the expression of AQP4-M1 and histone deacetylase3, reduced AQP4-M1/M23 ratio, and increased microRNA-130a expression in the cerebral cortex of APP/PS1 mice. In vitro, β-hydroxybutyrate was found to down-regulate the expression of AQP4-M1 and histone deacetylase3, reduce AQP4-M1/M23 ratio, and increase AQP4-M23 and microRNA-130a expression in 2 μM Aβ treated U251 cells. Interestingly, on the contrary to the result observed in 2 μM Aβ treated cells, AQP4 expression was obviously decreased in cells exposed to 10 μM Aβ. MicroRNA-130a mimic decreased the expression of AQP4-M1 and the ratio of AQP4-M1/M23, as well as silencing histone deacetylase3 caused the up-regulation of AQP4 and microRNA-130a, and the reduction of AQP4-M1/M23 ratio in U251 cells. In conclusion, intermittent fasting exhibits beneficial effects against Alzheimer’s disease. The mechanism may be associated with recovery of AQP4 polarity, resulting from the reduction of AQP4-M1/M23 ratio. Furthermore, β-hydroxybutyrate may partly mediate the effect of intermittent fasting on the reduction of AQP4-M1/M23 ratio in Alzheimer’s disease, in which microRNA-130a and histone deacetylase3 may be implicated.